MO201ANALYSIS OF USAGE OF SODIUM ZIRCONIUM CYCLOSILICATE (SZC) AT HULL UNIVERSITY TEACHING HOSPITALS. (29th May 2021) - Acquaye, Aaron; Babatunde-Ige, Tobi; Medlinskiene, Kristina; Choo, Stephanie; Bhandari, Sunil
Abstract: Background and Aims: Renin Angiotensin Aldosterone System (RASS) inhibitor therapy is key to the management of several chronic long term conditions; however, RAAS inhibitors can cause hyperkalaemia and thus limiting its use. Sodium zirconium cyclosilicate, was approved in the UK as part of the management of hyperkalaemia in adults. Although the efficacy and safety of SZC has been demonstrated in clinical trials, there isn't an abundance of data of its use in clinical practice. This study investigated the efficacy and safety of SCZ in the short-term management of hyperkalaemia in patients admitted acutely to hospital. Method: This retrospective study analysed prescriptions and medical notes of patients who received SCZ treatment between June and December 2020 at Hull University Teaching Hospitals. Eligible patients (>16years and received SCZ) were identified from pharmacy dispensing data. Data collected included patient demographics, prescribed medication that could affect serum potassium levels prior to starting SZC, indication, dose of SCZ, potassium level at start and 72hrs after treatment and if the patient was on renal replacement therapy (RRT). In addition, speciality of the prescriber and reported adverse effects were noted. Data analysis was descriptive. Results: During the study period, SZC was prescribed to 59 patients on 73 different occasions. Fifty-two (71%) were male, mean age was 58 years ( range 17 – 88 years ). Twenty-two patients (37%) were on RASS inhibitors, six patients on a potassium sparing diuretic, and 21 on a beta-blocker before treatment with SZC. Thirteen patients (22%) were on a combination of at least two of these medicines. Nineteen patients (32%) were on haemodialysis and four patients (7%) were on peritoneal dialysis (PD) prior to treatment with SZC. The documented reason for SZC use included hyperkalaemia secondary to dialysis access failure, acute kidney injury, pharmacotherapy induced hyperkalaemia and pre-emptive prescribing to allow time to create a new RRT access. Thirty-three (56%) patients had their serum potassium level checked at start and 72hrs after treatment with SZC. The remaining patients had their biochemical profiles checked more than 72 hours after starting SZC with inconsistent time frames and thus, were excluded from the further analysis. In haemodialysis patients, the median serum potassium level at start of treatment with SZC was 5.7mmol/L ( range 4.6mmol/L – 6.3mmol/L ) while in PD patients the median potassium level 6.4mmol/L (range 4.4mmol/L – 6.4mmol/L ). The mean decrease in serum potassium was 0.73mmol/L ( range 0.1mmolo/L – 3mmol/L ) and 1.7mmol/L ( range 0.1 -1.6mmol/L ) in HD and PD patients respectively. For patients not on RRT prior to treatment with SZC, and median serum potassium level at start of treatment was 6.0mmol/L ( range 5.5mmol/L – 6.7mmol/L ). In these patients, a mean decrease in serum potassium of 1.1mmol/L ( range 0.2mmol/L – 2.4mmol/L ) was observed. Twenty-three patients (70%) received 10g and ten patients received the 5g dose of SZC. Patients who had the 10g doses had a mean reduction in serum potassium of 1.0mmol/L (range 0.1mmol/L - 3.0mmol/L) and patients who received 5g doses had a mean reduction of 0.97mmol/L (range 0.2mmol/L – 1.9mmol/L ) over the 72-hour period. There were no reported side effects. It was found that SZC was initiated by a range of specialities (see Figure 1 ). The nephrology team accounted for the majority (45%) of prescriptions. Notably, the cardiology team initiated only one prescription. Conclusion: Our data from clinical practice indicates that SZC is effective and well-tolerated treatment in the management of hyperkalaemia. Our results also suggest that the reduction in potassium level was not vastly different for patients started on the 5g dose vs the 10g dose but this requires further research with larger study sample sizes. Limitations of the study included small sample size and retrospective nature of the study.